STRATEGI EVANGELISASI DIGITAL MELALUI SOSIAL TERHADAP GENERASI Z: SEBUAH PENDEKATAN KONTEKSTUAL DALAM PEWARTAAN INJIL - Marzuki, Calvien; Matteuw, Triatno; Darundas, Jalia Christyanti (PT. Giat Konseling Nusantara, 2025)
The advancement of information and communication technology has brought about significant transformations in social interaction patterns, including in the practice of Christian faith proclamation. Generation Z, as a digital-native generation, shows a strong preference for social media as the main medium for receiving information and forming religious identity. This study aims to examine digital evangelization strategies that are contextual and adaptive to the characteristics and socio-cultural dynamics of this generation. With a descriptive-qualitative approach based on literature studies, this paper highlights the importance of integrating theological values ​​with creative and relational digital communication methods. Evangelization in the digital era is not only about the distribution of messages of faith, but also demands authentic and dialogical involvement in cyberspace. Therefore, contextual strategies are urgent in bridging the proclamation of the Gospel with the digital reality of generation Z.